Determining the optimal application rate of chicken manure for agricultural land through Phosphorus sorption-desorption analyses in Andisols of Wonokitri, East Java, Indonesia - Noor, Muhammad Yussaq; Hartono, Arief; Nugroho, Budi (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2023)
Phosphorus (P) is a macro-essential element extensively used in agricultural production. Andisols, commonly found in Indonesia, serve as agricultural areas with high, excessive, and continuous organic matter input. However, the propensity of the soil for P leaching poses a potential risk of water pollution and eutrophication in the watershed area. This study aimed to evaluate the impact of the application rate of organic matter, specifically chicken manure, often employed in agricultural activities related to Andisols. The experiment involved observing P sorption, P desorption, P sorption kinetics, and P uptake by wheat (Triticum aestivum) in soil incubated with chicken manure added at various rates of 0, 10, 20, 30, and 40 t ha-1. The incubation stages were conducted for 14 days at room temperature (27°C) and soil moisture was maintained within field capacity. The data collected were analyzed using Langmuir isotherm for P sorption and desorption, and first-order kinetics for P sorption kinetics. The results showed that the chicken manure addition at 10-40 t ha-1 significantly reduced P bonding energy in Andisols, but failed to decrease the sorption maxima value due to accumulated P from previous applications performed. The application of 20 t ha-1 (CM20) of chicken manure was found to be the optimal rate, displaying high P uptake and reduced bonding energy, while rates above 20 t ha-1 showed no significant difference in P uptake and bonding energy levels. Therefore, CM20 was recommended to increase P availability and prevent P movement into water bodies, promoting sustainable agricultural practices.